Studi Studi Literatur Evaluasi Implementasi Kebijakan Pembangunan Proyek Strategis Nasional (PSN) Kereta Api Makassar - Parepare - Ahmad Dzaky; Armin Arsyad; Ariana Yunus (Jurnal Administrasi Politik dan Sosial, 2026)
The Makassar–Parepare Railway National Strategic Project (PSN) is a strategic initiative mandated by the central government under Presidential Regulation No. 109 of 2020. The project aims to promote equitable development and enhance transportation infrastructure, particularly across the island of Sulawesi. Additionally, this railway development marks the initial phase in connecting regions within Sulawesi. The project was inaugurated in 2023 by President Joko Widodo; however, only a portion of the route stretching from Mandai to Garongkong Port has been made operational, while several other segments remain under construction. These conditions necessitate an evaluation of how government policy has been implemented. Using an on-going evaluation approach, this paper discusses literature-based assessments related to the policy implementation of the project. The study employs a qualitative descriptive method with a library research approach. The findings reveal several key issues, including challenges in the land acquisition process, insufficient coordination among actors, a development model that remains distant from public accessibility, and evaluation dimensions shaped by social and environmental factors.